Pengaruh Musik terhadap Kualitas Tidur pada Mahasiswa Fakultas Kedokteran Universitas Kristen Krida Wacana - Syela C Akasian; Flora Rumiati; William William (Jurnal Kedokteran Meditek, 2020)
Music is an enjoyable tune, generally used to relieve a person's fatigue or stress. Scientifically, music can also influence sleep quality, especially among elderly people. The purpose of this study was to determine whether music had an effect on sleep quality among young adults, particularly medical students who usually had poor sleep quality. The research design used was a cross-sectional study with a simple random sampling technique. The subjects of this study were the 2018 Ukrida medical students. Pittsburgh Sleep Quality Index (PSQI) questionnaire and additional questionnaires to see the music listening habits of students were distributed simultaneously during class. The results of the research conducted showed that from a total of 96 students, most of them had a poor sleep quality, namely 88 (91.7%) students. Three of 48 students who had a habit of listening to music before going to sleep had good sleep quality. Five of eight students who had good sleep quality had no habit of listening to the music before going to sleep. The Chi Square test results showed that there was no significant relationship between music and sleep quality among students (p = 0.714).